Membrane electrode assembly for solid polymer fuel cell, and solid polymer fuel cell
By stacking the electrode catalyst layer on both sides of the polymer electrolyte membrane and using a hydrocarbon-based polymer electrolyte membrane and a fibrous substance, the problem of poor adhesion between the electrode catalyst layer and the polymer electrolyte membrane in the traditional method is solved, and high performance and durability are achieved membrane electrode joint.
Patent Information
- Application Number
- CN202411283358.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-12-04
- Filing Date
- 2019-01-30
- Publication Date
- 2024-12-13
AI Technical Summary
In the traditional method of manufacturing membrane electrode bonds, the adhesiveness between the electrode catalyst layer and the polymer electrolyte membrane is poor, and voids are prone to occur, resulting in reduced power generation performance and durability problems.
The electrode catalyst layer is laminated on both sides of the polymer electrolyte membrane. The electrode catalyst layer contains a catalyst, carbon particles and a polymer electrolyte. The height of the void at the interface in the vertical direction is less than 0.5 μm and in the parallel direction. The width is 10 μm or less, and a hydrocarbon-based polymer electrolyte membrane and a fibrous substance are used to improve adhesion.
Good adhesion between the electrode catalyst layer and the polymer electrolyte membrane is achieved, power generation performance and durability are improved, and performance reduction is avoided due to interface resistance and water overflow.
Smart Images

Figure CN119133539A_ABST
Abstract
Description
[0001] The present application is a divisional application of application number 2019800102699, application date January 30, 2019, and invention name “Membrane electrode assembly for solid polymer fuel cell and solid polymer fuel cell”. Technical Field
[0002] The present invention relates to a membrane electrode assembly for a solid polymer fuel cell and a solid polymer fuel cell. Background Art
[0003] Solid polymer fuel cells have a structure in which a polymer electrolyte membrane is sandwiched between a cathode electrode catalyst layer and an anode electrode catalyst layer. Since they operate at room temperature and have a short startup time, they are expected to be used as power sources for automobiles and stationary power sources.
[0004] As a conventional method for manufacturing a membrane electrode assembly, there is known a method in which a catalyst ink consisting of carbon particles loaded with a catalyst, a polymer electrolyte and a solvent is applied to a transfer substrate or a gas diffusion layer, and then hot-pressed onto a polymer electrolyte membrane to produce a membrane electrode assembly.
[0005] However, in the conventional transfer method for manufacturing a membrane electrode assembly, the adhesion between the electrode catalyst layer and the polymer electrolyte membrane is reduced, and a gap is easily generated between the electrode catalyst layer and the polymer electrolyte membrane. Therefore, it is easy to cause a reduction in power generation performance due to interface resistance, or a reduction in power generation performance due to water clogging the gap and overflowing (flooding).
[0006] In order to solve such problems, various technical solutions have been proposed. For example, Patent Document 1 discloses a technology that forms concavities and convexities on the surface of a polymer electrolyte membrane by spraying ceramic particles, and forms an electrode catalyst layer on the concavities and convexities so that the concavities and convexities sink into the surface of the catalyst layer, thereby improving adhesion. In addition, Patent Document 2 discloses a technology that improves adhesion by irradiating a laser at the interface of the electrode catalyst layer and the polymer electrolyte membrane and heating them to make them hot-pressed.
[0007] However, the techniques disclosed in Patent Documents 1 and 2 may reduce the durability of the membrane electrode assembly and may also cause a reduction in yield or increase in cost due to the complexity of the manufacturing process.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2007-26836
[0011] Patent Document 2: Japanese Patent Application Publication No. 2009-176518 Summary of the invention
[0012] [Problems to be Solved by the Invention]
[0013] An object of the present invention is to provide a membrane electrode assembly for a polymer electrolyte fuel cell having good adhesion at the interface between an electrode catalyst layer and a polymer electrolyte membrane, and a polymer electrolyte fuel cell.
[0014] [Means for solving the problem]
[0015] The main contents of a membrane electrode assembly for a solid polymer fuel cell involved in one embodiment of the present invention are: a membrane electrode assembly for a solid polymer fuel cell, wherein electrode catalyst layers are stacked on both sides of a polymer electrolyte membrane, the polymer electrolyte membrane contains a hydrocarbon-based polymer electrolyte, and there is no void portion at the interface between the polymer electrolyte membrane and the electrode catalyst layer.
[0016] The main contents of the membrane electrode assembly for solid polymer fuel cells involved in other embodiments of the present invention are: a membrane electrode assembly for solid polymer fuel cells, wherein electrode catalyst layers are stacked on both sides of the polymer electrolyte membrane, the electrode catalyst layers contain catalysts, carbon particles, and polymer electrolytes, the polymer electrolyte membrane contains a hydrocarbon-based polymer electrolyte, and at least one void portion is formed at the interface between the electrode catalyst layer and the polymer electrolyte membrane. When a cross-section formed by cutting the membrane electrode assembly for solid polymer fuel cells with a plane perpendicular to the interface is observed using a scanning electron microscope, the length of the void portion in a direction perpendicular to the interface, that is, the height, is set to h, and the length of the void portion in a direction parallel to the interface, that is, the width, is set to w. In each interface on both sides of the polymer electrolyte membrane, the height h of the void portion is less than 0.5 μm, and the total width w of the void portion existing in an area with a length of 30 μm in a direction parallel to the interface is less than 10 μm.
[0017] The main contents of the membrane electrode assembly for solid polymer fuel cells involved in further other embodiments of the present invention are: a membrane electrode assembly for solid polymer fuel cells, wherein electrode catalyst layers are stacked on both sides of the polymer electrolyte membrane, the electrode catalyst layers contain catalysts, carbon particles, polymer electrolytes, and fibrous substances, and there are no voids at the interface between the electrode catalyst layer and the polymer electrolyte membrane.
[0018] The main contents of the membrane electrode assembly for solid polymer fuel cells involved in further other embodiments of the present invention are: a membrane electrode assembly for solid polymer fuel cells, wherein electrode catalyst layers are stacked on both sides of the polymer electrolyte membrane, the electrode catalyst layers contain catalysts, carbon particles, polymer electrolytes and fibrous substances, at least one void portion is formed at the interface between the electrode catalyst layer and the polymer electrolyte membrane, and when a cross-section formed by cutting the membrane electrode assembly for solid polymer fuel cells with a plane perpendicular to the interface is observed using a scanning electron microscope, the length of the void portion in a direction perpendicular to the interface, that is, the height, is set to h, and the length of the void portion in a direction parallel to the interface, that is, the width, is set to w, in each interface on both sides of the polymer electrolyte membrane, the height h of the void portion is less than 0.5 μm, and the total width w of the void portion existing in an area with a length of 30 μm in a direction parallel to the interface is less than 10 μm.
[0019] A polymer electrolyte fuel cell according to still another aspect of the present invention mainly comprises the polymer electrolyte fuel cell membrane electrode assembly according to one or other aspects described above.
[0020] [Effects of the Invention]
[0021] According to the present invention, it is possible to provide a membrane electrode assembly for a polymer electrolyte fuel cell having good adhesion at the interface between an electrode catalyst layer and a polymer electrolyte membrane, and a polymer electrolyte fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] [ Figure 1 ] is an exploded perspective view showing the internal structure of a solid polymer fuel cell involved in one embodiment of the present invention.
[0023] [ Figure 2 ] is a diagram illustrating the structure of a membrane electrode assembly for a solid polymer fuel cell according to one embodiment of the present invention.
[0024] [ Figure 3 ] is a diagram illustrating the structure of a membrane electrode assembly for a solid polymer fuel cell according to another embodiment of the present invention.
[0025] [ Figure 4 ] is a schematic cross-sectional view illustrating an example of the structure of the interface between the electrode catalyst layer and the polymer electrolyte membrane.
[0026] [ Figure 5 ] is a schematic cross-sectional view illustrating another example of the structure of the interface between the electrode catalyst layer and the polymer electrolyte membrane. DETAILED DESCRIPTION
[0027] Hereinafter, the embodiments of the present invention will be described with reference to the accompanying drawings. It should be noted that the present embodiments are not limited to the embodiments described below, and the embodiments may be modified by design changes based on the knowledge of those skilled in the art, and the embodiments with such modifications are also included in the scope of the present embodiments.
[0028] In addition, in the following detailed description, specific details are described in order to provide a complete understanding of the embodiments of the present invention. However, it should be understood that one or more embodiments can be implemented without these specific details. In addition, in order to simplify the drawings, known structures and devices are sometimes shown with omitted figures.
[0029] (Structure of solid polymer fuel cell)
[0030] like Figure 1 As shown, a pair of electrode catalyst layers 3A and 3F facing each other with the polymer electrolyte membrane 2 sandwiched therebetween are arranged on both sides of the polymer electrolyte membrane 2 constituting the solid polymer fuel cell 1. A gas diffusion layer 4A is arranged on the surface of the electrode catalyst layer 3A opposite to the surface facing the polymer electrolyte membrane 2, and a gas diffusion layer 4F is arranged on the surface of the electrode catalyst layer 3F opposite to the surface facing the polymer electrolyte membrane 2, and the gas diffusion layers 4A and 4F are arranged in a manner facing each other with the polymer electrolyte membrane 2 and the pair of electrode catalyst layers 3A and 3F sandwiched therebetween.
[0031] A separator 5A is disposed on the surface of the gas diffusion layer 4A opposite to the surface facing the electrode catalyst layer 3A, wherein the separator 5A has a gas flow path 6A for the flow of reaction gas on the main surface opposite to the surface, and a cooling water path 7A for the flow of cooling water on the main surface opposite to the main surface having the gas flow path 6A. Further, a separator 5F is disposed on the surface of the gas diffusion layer 4F opposite to the surface facing the electrode catalyst layer 3F, wherein the separator 5F has a gas flow path 6F for the flow of reaction gas on the main surface opposite to the surface, and a cooling water path 7F for the flow of cooling water on the main surface opposite to the main surface having the gas flow path 6F. Hereinafter, when there is no need to distinguish, the electrode catalyst layers 3A and 3F may be simply described as "electrode catalyst layer 3".
[0032] Figure 2 Schematic cross-sectional view showing an example of the structure of the electrode catalyst layer according to this embodiment. Figure 2As shown, the electrode catalyst layer 8 involved in this embodiment is bonded to the surface of the polymer electrolyte membrane 9, and is composed of a catalyst 10, carbon particles 11 as a conductive carrier, and a polymer electrolyte 12. Then, in the electrode catalyst layer 8, the portion where any of the constituent elements of the catalyst 10, the carbon particles 11, and the polymer electrolyte 12 does not exist becomes a pore.
[0033] In addition, the polymer electrolyte membrane 9 involved in this embodiment may be a hydrocarbon-based polymer electrolyte membrane composed of a hydrocarbon-based polymer electrolyte or a hydrocarbon-based polymer electrolyte membrane composed only of a hydrocarbon-based polymer electrolyte. In this embodiment, the so-called "hydrocarbon-based polymer electrolyte membrane" refers to a membrane that contains, for example, more than 50% by mass of a hydrocarbon-based polymer electrolyte described later relative to the total mass of the polymer electrolyte membrane 9.
[0034] (Manufacture of catalyst ink)
[0035] Next, a method for producing a catalyst ink for forming the electrode catalyst layers 3, 8 (electrode catalyst layers for solid polymer fuel cells) of the solid polymer fuel cell 1 according to the present embodiment is described. First, carbon particles 11 carrying a catalyst 10 are mixed and dispersed in a dispersion medium to obtain a catalyst particle slurry.
[0036] As the catalyst 10, for example, platinum group elements (platinum, palladium, ruthenium, iridium, rhodium, osmium), metals such as iron, lead, copper, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, aluminum, and alloys, oxides, composite oxides, carbides, etc. of these metals can be used.
[0037] As the carbon particles 11, any substance can be used as long as it has conductivity and is not affected by the catalyst 10 and can load the catalyst 10, but carbon particles are generally used. As carbon particles, for example, carbon black, graphite, black lead, activated carbon, carbon nanotubes, carbon nanofibers and fullerenes can be used. When the particle size of the carbon particles is too small, it is difficult to form an electron conduction path. In addition, when the particle size is too large, the gas diffusion of the electrode catalyst layer 8 is reduced, or the utilization rate of the catalyst is reduced. Therefore, the particle size of the carbon particles is preferably in the range of 10 nm to 1000 nm. More preferably, it is in the range of 10 nm to 100 nm.
[0038] As the dispersion medium, for example, water or any one of alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutyl alcohol, tert-butyl alcohol, and amyl alcohol can be selected and used. In addition, a solvent obtained by mixing two or more of the above solvents can also be used. For example, a bead mill, a planetary mixer, a disperser, and the like can be used for mixed dispersion.
[0039] Next, a polymer electrolyte 12 is added to the catalyst particle slurry obtained by the above method. As the polymer electrolyte 12, for example, a fluorine-based polymer electrolyte or a hydrocarbon-based polymer electrolyte can be used. As a fluorine-based polymer electrolyte, for example, Nafion (registered trademark) manufactured by DuPont, Flemion (registered trademark) manufactured by Asahi Glass (Strain), Aciplex (registered trademark) manufactured by Asahi Kasei (Strain), Gore Select (registered trademark) manufactured by Goa, etc. can be used. As a hydrocarbon-based polymer electrolyte, for example, electrolytes such as sulfonated polyether ketone, sulfonated polyether sulfone, sulfonated polyether ether sulfone, sulfonated polysulfide, and sulfonated polyphenylene can be used. Among these, it is preferred to use Nafion (registered trademark) materials manufactured by DuPont as the polymer electrolyte.
[0040] (Manufacturing of membrane electrode assembly)
[0041] The membrane electrode assembly is manufactured by bonding the electrode catalyst layer 3 to both sides of the polymer electrolyte membrane 2. At this time, as a method for bonding the electrode catalyst layer 3 to the polymer electrolyte membrane 2, there is, for example, the following method: using a transfer substrate with an electrode catalyst layer coated with a catalyst ink on the transfer substrate, the surface of the electrode catalyst layer of the transfer substrate with the electrode catalyst layer is contacted with the polymer electrolyte membrane and heated and pressurized, thereby bonding the polymer electrolyte membrane 2 and the electrode catalyst layer 3. In the case of bonding the polymer electrolyte membrane 2 and the electrode catalyst layer 3 by contacting and heating and pressurizing the transfer substrate with the electrode catalyst layer, the pressure and temperature applied to the electrode catalyst layer 3 sometimes affect the power generation performance of the membrane electrode assembly. In order to obtain a membrane electrode assembly with high power generation performance, it is desirable that the pressure applied to the stack is within the range of 0.1 MPa to 20 MPa. When the pressure applied to the stack is greater than 20 MPa, the electrode catalyst layer 3 becomes overly compressed, and when it is less than 0.1 MPa, the bonding between the electrode catalyst layer 3 and the polymer electrolyte membrane 2 is reduced, thereby reducing the power generation performance. In order to improve the bonding property of the interface between the polymer electrolyte membrane 2 and the electrode catalyst layer 3 and suppress the interface resistance, the bonding temperature is preferably set to near the glass transition temperature of the polymer electrolyte 12 of the polymer electrolyte membrane 2 or the electrode catalyst layer 3 .
[0042] However, according to the above method, the adhesion between the electrode catalyst layer 3 and the polymer electrolyte membrane 2 is poor, and a void portion is easily formed at the interface between the electrode catalyst layer 3 and the polymer electrolyte membrane 2. Then, there is a tendency to easily cause problems such as a decrease in power generation performance due to interface resistance or a decrease in power generation performance due to overflow caused by water flowing into the void portion being blocked.
[0043] On the other hand, the membrane electrode assembly can also be manufactured by directly applying the catalyst ink on the surface of the polymer electrolyte membrane 2 and then removing the solvent component (dispersion medium) from the coating of the catalyst ink. As a method for directly applying the catalyst ink on the polymer electrolyte membrane 2, various coating methods such as die coating, roller coating, curtain coating, spray coating, screen printing, etc. can be used. In particular, the die coating method is preferred. The die coating method can keep the film thickness in the middle part of the coating stable, so it can also be used for intermittent coating. Furthermore, as a method for drying the applied catalyst ink, for example, a hot air oven, IR (far infrared) drying, hot plate, reduced pressure drying, etc. can be used. The drying temperature is in the range of 40°C to 200°C, preferably in the range of 40°C to 120°C. The drying time is in the range of 0.5 minutes to 1 hour, preferably in the range of 1 minute to 30 minutes.
[0044] According to this method, the adhesion between the electrode catalyst layer 3 and the polymer electrolyte membrane 2 is good, and the above-mentioned problem is unlikely to occur. However, in the method of directly applying the catalyst ink on the polymer electrolyte membrane 2, wrinkles or cracks are easily generated in the applied electrode catalyst layer 3 due to the swelling of the polymer electrolyte membrane 2, which easily leads to the problem of reduced power generation performance and reduced durability. In particular, in fluorine-based polymer electrolyte membranes, due to the low glass transition temperature, swelling is also easily generated, so in the process of directly applying the catalyst ink on the polymer electrolyte membrane 2 and drying, wrinkles or cracks are easily generated in the electrode catalyst layer 3.
[0045] In contrast, hydrocarbon polymer electrolytes have a high glass transition temperature and are less likely to swell in the process of directly coating the catalyst ink on the polymer electrolyte membrane 2 and drying it. Therefore, as in the present embodiment, by using a hydrocarbon polymer electrolyte membrane in which a hydrocarbon polymer electrolyte is included in the polymer electrolyte membrane 2, wrinkles or cracks are less likely to occur in the electrode catalyst layer 3 even when the catalyst ink is directly coated on the polymer electrolyte membrane 2, a membrane electrode assembly having good adhesion between the electrode catalyst layer 3 and the polymer electrolyte membrane 2 can be obtained. It should be noted that, as the hydrocarbon polymer electrolyte included in the hydrocarbon polymer electrolyte membrane, for example, electrolytes such as sulfonated polyether ketone, sulfonated polyether sulfone, sulfonated polyether ether sulfone, sulfonated polysulfide, and sulfonated polyphenylene can be used.
[0046] Hereinafter, the above-mentioned effects exerted when a hydrocarbon-based polymer electrolyte membrane is used as the polymer electrolyte membrane 2 will be described in detail.
[0047] As the catalyst ink used in manufacturing the electrode catalyst layer, an ink containing a catalyst and an alcohol is sometimes used, but the catalyst ink has the risk of ignition (combustion) of the ink itself. Therefore, when using the catalyst ink, water is sometimes added to the catalyst ink to reduce the flammability (combustibility) of the ink itself.
[0048] By adding water to the catalyst ink, the flammability (combustibility) of the ink itself can be reduced, but there is also a disadvantage that the drying speed of the catalyst ink is reduced. Therefore, when using the catalyst ink to which water is added to manufacture the electrode catalyst layer, it is required to increase the drying temperature of the catalyst ink from the normal temperature of about 80°C to, for example, about 90°C.
[0049] Here, among the fluorine-based polymer electrolyte membranes used as polymer electrolyte membranes, there are many electrolyte membranes with low glass transition temperatures. Therefore, when using a fluorine-based polymer electrolyte membrane as a polymer electrolyte membrane, the drying temperature of the catalyst ink sometimes exceeds the glass transition temperature of the fluorine-based polymer electrolyte membrane. In this case, the fluorine-based polymer electrolyte membrane swells, and the adhesion between the electrode catalyst layer and the fluorine-based polymer electrolyte membrane tends to decrease.
[0050] In contrast, the glass transition temperature of the hydrocarbon polymer electrolyte membrane used in the present embodiment is mostly higher than that of the fluorine-based polymer electrolyte membrane. For example, the glass transition temperature of the hydrocarbon polymer electrolyte membrane is above 100 degrees. Therefore, when a hydrocarbon polymer electrolyte membrane is used as a polymer electrolyte membrane, even if the drying temperature of the catalyst ink is increased to (for example) about 90°C, its drying temperature rarely exceeds the glass transition temperature of the hydrocarbon polymer electrolyte membrane. As a result, the swelling of the hydrocarbon polymer electrolyte membrane becomes extremely small, and the adhesion between the electrode catalyst layer and the hydrocarbon polymer electrolyte membrane tends to be improved compared to the adhesion between the electrode catalyst layer and the fluorine-based polymer electrolyte membrane.
[0051] On the other hand, as a method for directly applying the catalyst ink on the polymer electrolyte membrane 2 in a manner that does not generate wrinkles and cracks on the fluorine-based polymer electrolyte membrane, there is a method of adding a fibrous substance 13 to the catalyst ink. If the fibrous substance 13 is added to the catalyst ink, the strength of the electrode catalyst layer 3 is improved, so even if the catalyst ink is directly applied to the polymer electrolyte membrane 2, it is difficult to generate wrinkles or cracks in the electrode catalyst layer 3, so that a membrane electrode assembly with good adhesion between the electrode catalyst layer 3 and the polymer electrolyte membrane 2 can be obtained. It should be noted that as a fluorine-based polymer electrolyte, a polymer electrolyte having a tetrafluoroethylene skeleton, such as "Nafion (registered trademark)" manufactured by DuPont can be used.
[0052] Figure 3 An example of the structure of a membrane electrode assembly for a polymer electrolyte fuel cell is shown, which includes an electrode catalyst layer 3 formed by adding a fibrous substance 13 to a catalyst ink.
[0053] Electron conductive fibers and proton conductive fibers can be used as the fibrous material 13. As the fibrous material 13, one of the following fibers may be used alone or two or more thereof may be used in combination, and electron conductive fibers and proton conductive fibers may be used in combination.
[0054] As the electron conductive fiber involved in the present embodiment, for example, carbon fiber, carbon nanotube, carbon nanohorn, conductive polymer nanofiber, etc. can be listed. In particular, from the aspects of conductivity and dispersibility, carbon nanofiber is preferred. In addition, by using electron conductive fibers with catalytic function, the amount of catalyst composed of precious metals can be reduced, so it is more preferred. In the case of being used as an air electrode of a solid polymer fuel cell, for example, a carbon alloy catalyst made of carbon nanofiber can be listed. In addition, the electrode active material for the oxygen reduction electrode can also be processed into a fibrous material, for example, a material containing at least one transition metal element selected from Ta, Nb, Ti, and Zr can be used. Partial oxides of carbonitrides of these transition metal elements, or conductive oxides or conductive oxygen-nitrogen compounds of these transition metal elements can be listed.
[0055] As the proton conductive fiber involved in the present embodiment, it is sufficient to process the polymer electrolyte with proton conductivity into a fiber shape, for example, a fluorine-based polymer electrolyte or a hydrocarbon-based polymer electrolyte can be used. As a fluorine-based polymer electrolyte, for example, Nafion (registered trademark) manufactured by DuPont, Flemion (registered trademark) manufactured by Asahi Glass (Co., Ltd.), Aciplex (registered trademark) manufactured by Asahi Kasei (Co., Ltd.), Gore Select (registered trademark) manufactured by Goa, etc. can be used. As a hydrocarbon-based polymer electrolyte, for example, electrolytes such as sulfonated polyether ketone, sulfonated polyether sulfone, sulfonated polyether ether sulfone, sulfonated polysulfide, and sulfonated polyphenylene can be used. Among these, Nafion (registered trademark) materials manufactured by DuPont can be preferably used as polymer electrolytes.
[0056] The fiber diameter of the fibrous material 13 is preferably in the range of 0.5 nm to 500 nm, more preferably in the range of 5 nm to 200 nm. By setting the fiber diameter in this range, the pores in the electrode catalyst layer 3 can be increased, thereby achieving high output.
[0057] In addition, the fiber length of the fibrous material 13 is preferably in the range of 1 μm to 40 μm, and more preferably in the range of 1 μm to 20 μm. By setting the fiber length within this range, the strength of the electrode catalyst layer 3 can be increased, thereby suppressing the generation of wrinkles or cracks during formation. In addition, the pores in the catalyst layer can be increased, thereby achieving high output power.
[0058] It should be noted that, in the above-mentioned embodiment, the case where the catalyst ink to which the fibrous substance 13 is added is applied on the fluorine-based polymer electrolyte membrane to form a solid polymer fuel cell membrane electrode assembly is described, but the present invention is not limited thereto. For example, the catalyst ink to which the fibrous substance 13 is added may also be applied on the hydrocarbon-based polymer electrolyte membrane to form a solid polymer fuel cell membrane electrode assembly.
[0059] Here, using Figure 4 The voids 14 in the present embodiment are described in detail. Although it is preferred that there are no voids 14 at the interface between the electrode catalyst layer 8 and the polymer electrolyte membrane 9, there are cases where voids 14 are generated. Here, the "no voids 14" means that even when the magnification of the scanning electron microscope (SEM) is set to 4000 times and the interface between the electrode catalyst layer 8 and the polymer electrolyte membrane 9 is observed, the presence of the voids 14 cannot be confirmed at the interface.
[0060] As a cause of the generation of the voids 14, microscopic irregularities are generated on the surface of the electrode catalyst layer 8 when the electrode catalyst layer 8 is formed on a transfer substrate (not shown). As a result, when the electrode catalyst layer 8 is transferred onto the polymer electrolyte membrane 9, voids 14 are generated at the interface between the polymer electrolyte membrane 9 and the electrode catalyst layer 8 due to the irregularities.
[0061] In addition, even in the method of directly coating the catalyst ink on the polymer electrolyte membrane 9 without passing through a transfer substrate, when wrinkles or cracks are generated in the electrode catalyst layer 8 formed by coating, corresponding voids 14 are generated at the interface between the polymer electrolyte membrane 9 and the electrode catalyst layer 8.
[0062] In particular, when there is a void 14 whose length in a direction perpendicular to the interface, i.e., height h, exceeds 0.5 μm at the interface between the electrode catalyst layer 8 and the polymer electrolyte membrane 9, or when there are a large number of voids 14 whose height h is less than 0.5 μm in a certain area, problems such as reduced power generation performance and reduced durability are likely to occur.
[0063] However, in a fuel cell, water is generated by power generation, and when the fuel cell is used, the generated water penetrates into the polymer electrolyte membrane 9, causing the polymer electrolyte membrane 9 to swell. Therefore, even if there is a void 14 between the electrode catalyst layer 8 and the polymer electrolyte membrane 9, if the height h of the void 14 is less than 0.5 μm, and the total width w of the void 14 existing in the region with a length l of 30 μm in the direction parallel to the interface is less than 10 μm, it is found that the void 14 is buried due to the swelling of the polymer electrolyte membrane 9.
[0064] exist Figure 4 In the illustrated example, two voids 14, 14 exist in a region having a length l of 30 μm in a direction parallel to the interface, and the total width w1, w2 of the two voids 14, 14 is 10 μm or less.
[0065] It should be noted that in this embodiment, when a cross-section formed by cutting a membrane electrode assembly for a solid polymer fuel cell in a plane perpendicular to the interface is observed using an SEM, the length of the gap portion 14 in a direction perpendicular to the interface is set to a height h, and the length of the gap portion 14 in a direction parallel to the interface is set to a width w.
[0066] Therefore, by making the void 14 generated at the interface between the polymer electrolyte membrane 9 and the electrode catalyst layer 8 satisfy the above two numerical conditions, it is difficult to cause the reduction in power generation performance due to the interface resistance between the electrode catalyst layer 8 and the polymer electrolyte membrane 9, or the reduction in power generation performance due to the blockage of water flowing to the void 14 and overflow. The height h of the void 14 is required to be 0.5 μm or less, and more preferably 0.3 μm or less. If the height h of the void 14 is 0.3 μm or less, it is easy to bury the void 14 even if the swelling rate of the polymer electrolyte membrane 9 is reduced.
[0067] When the total width w of the voids 14 existing in a region with a length l of 30 μm in a direction parallel to the interface exceeds 10 μm, the voids 14 become wider and are difficult to fill even if the polymer electrolyte membrane 9 swells.
[0068] It should be noted that the void 14 can be confirmed by observing a cross section formed by cutting the solid polymer fuel cell membrane electrode assembly with a plane perpendicular to the interface using SEM. The type of SEM is not particularly limited, and for example, S-4800 manufactured by Hitachi High Tech Nologics Co., Ltd. can be used. In addition, the magnification during SEM observation is not particularly limited, and for example, it can be 4000 times.
[0069] If the height h and width w of the void 14 existing at the interface between one surface of the polymer electrolyte membrane 9 and the electrode catalyst layer 8 are within the above-mentioned range, the above-mentioned effect can be achieved, but it is preferred that the height h and width w of the void 14 existing at the interface between both surfaces of the polymer electrolyte membrane 9 and the electrode catalyst layer 8 are within the above-mentioned range.
[0070] Further, if Figure 5 As shown, it is further preferred that: in the interface on both sides of the polymer electrolyte membrane 9, the voids 14 existing at the same position in the direction parallel to the interface sandwiching the polymer electrolyte membrane 9 or the voids 14 existing in a partially overlapping manner simultaneously satisfy the above range. That is, in the interface on both sides of the polymer electrolyte membrane 9, by making the voids 14 existing in the region with a length of 30 μm in the direction parallel to the interface satisfy the above two numerical conditions, the reaction efficiency on the anode side and the cathode side can be further improved.
[0071] The thickness of the electrode catalyst layer 8 is preferably 5 μm to 30 μm, and particularly preferably 20 μm or less. When the thickness of the electrode catalyst layer 8 is greater than 30 μm, more precisely, greater than 20 μm, cracks are likely to form in the electrode catalyst layer 8, and when the electrode catalyst layer 8 is used in a fuel cell, the diffusivity and conductivity of the gas or generated water are reduced, so that the output power may be reduced. When the thickness of the electrode catalyst layer 8 is thinner than 5 μm, the layer thickness is likely to deviate, and the catalyst and polymer electrolyte inside may sometimes become uneven.
[0072] In addition, for example, the ratio of the polymer electrolyte 12 in the electrode catalyst layer 8 is preferably the same as or about half of the weight of the carbon particles 11. In addition, the ratio of the fibrous substance 13 is preferably the same as or about half of the weight of the carbon particles 11. The solid content ratio of the catalyst ink is preferably as high as possible as long as it is within the range that can be applied on the film.
[0073] (Effects of this embodiment)
[0074] According to the present embodiment, it is possible to manufacture a membrane electrode assembly having good adhesion between the electrode catalyst layer 8 and the polymer electrolyte membrane 9 and excellent power generation performance and durability without using complicated steps.
[0075] Hereinafter, examples and comparative examples of the present invention will be described.
[0076] (Example 1)
[0077] A platinum-supported carbon catalyst (TEC10E50E, manufactured by Tanaka Kikinzoku Co., Ltd.), water, 1-propanol, and a polymer electrolyte (Nafion (registered trademark) dispersion, manufactured by Wako Junkyo Kogyo Co., Ltd.) were mixed, and each component was dispersed to a degree that was not excessively dispersed using a bead mill disperser to prepare a catalyst ink. The solid content ratio of the catalyst ink thus prepared was 10% by mass. It should be noted that the mass ratio of water to 1-propanol was set to 1:1. In addition, the conditions for dispersing each component using a bead mill disperser were set as follows. In addition, the following conditions are common to the following Examples and Comparative Examples.
[0078] Number of passes: 5 times
[0079] Ball (bead) diameter: 0.3mm
[0080] Stirrer peripheral speed: 10m / sec
[0081] In addition, hydrocarbon-based polymer electrolyte membranes are produced by sulfonating special engineering plastics using a known method.
[0082] The prepared catalyst ink was directly coated on both surfaces of a hydrocarbon-based polymer electrolyte membrane using a slot die coater and dried to form an electrode catalyst layer, thereby obtaining a membrane electrode assembly.
[0083] First, the membrane electrode assembly thus obtained was sliced using a microtome (manufactured by Leica, EMUC7 automatic microtome), and then the interface between the electrode catalyst layer and the polymer electrolyte membrane of the sliced membrane electrode assembly was observed using a SEM (manufactured by Hitachi HiTech Nologics, Ltd.) with a magnification of 4000 times.
[0084] In the membrane electrode assembly of Example 1, there is no void portion at the interface between the electrode catalyst layer and the polymer electrolyte membrane. Therefore, the adhesion between the electrode catalyst layer and the polymer electrolyte membrane is good, and good power generation performance and durability are exhibited.
[0085] (Example 2)
[0086] A membrane electrode assembly of Example 2 was obtained in the same manner as in Example 1 except that the coating amount of the electrode catalyst layer (catalyst ink) on the cathode side was doubled.
[0087] In the membrane electrode assembly of Example 2, there is no void at the interface between the electrode catalyst layer and the polymer electrolyte membrane. As a result, the adhesion between the electrode catalyst layer and the polymer electrolyte membrane is good, and good power generation performance and durability are exhibited.
[0088] (Example 3)
[0089] The membrane electrode assembly of Example 3 was obtained by the same procedure as Example 1 except that a planetary ball mill was used to disperse the catalyst ink. It should be noted that the conditions for dispersing the components using the ball mill were set as follows. In addition, the following conditions are common to the following Examples and Comparative Examples.
[0090] Dispersion time: 3 hours
[0091] Ball diameter: 3mm
[0092] Compared with the catalyst ink of Example 1 dispersed by a bead mill disperser, the dispersion degree of the catalyst ink of Example 3 is lower. As a result, at the interface between the electrode catalyst layer and the polymer electrolyte membrane of the membrane electrode assembly of Example 3, there are multiple voids with a height h of 0.3 μm to 0.4 μm, and the width w of the multiple voids in the region with a length of 30 μm in the direction parallel to the interface is 6 μm in total. The membrane electrode assembly of Example 3 has good power generation performance and durability.
[0093] (Example 4)
[0094] A membrane electrode assembly of Example 4 was obtained by the same procedure as in Example 1 except that an alloy-based carbon catalyst of platinum and cobalt was used instead of the platinum-supporting carbon catalyst.
[0095] Compared with the ink of Example 1, the catalyst ink of Example 4 had cracks in a part of the electrode catalyst layer when applied to the polymer electrolyte membrane. As a result, at the interface between the electrode catalyst layer and the polymer electrolyte membrane of the membrane electrode assembly of Example 4, there were multiple voids with a height h of 0.1 μm to 0.2 μm, and the width w of the multiple voids in the region with a length of 30 μm in the direction parallel to the interface was 10 μm in total. The membrane electrode assembly of Example 4 had good power generation performance and durability.
[0096] (Example 5)
[0097] A membrane electrode assembly of Example 5 was obtained by the same procedure as in Example 1 except that carbon nanofibers (VGCF-H (registered trademark), manufactured by Showa Denko K.K.) were mixed into the catalyst ink of Example 1.
[0098] In the membrane electrode assembly of Example 5, there was no void portion at the interface between the electrode catalyst layer and the polymer electrolyte membrane, so the adhesion between the electrode catalyst layer and the polymer electrolyte membrane was good, and good power generation performance and durability were exhibited.
[0099] (Example 6)
[0100] A membrane electrode assembly of Example 6 was obtained by the same procedure as in Example 3 except that carbon nanofibers (VGCF-H (registered trademark), manufactured by Showa Denko K.K.) were mixed into the catalyst ink of Example 3.
[0101] Compared with the catalyst ink of Example 3, the dispersion of the catalyst ink of Example 6 is lower. Therefore, at the interface between the electrode catalyst layer and the polymer electrolyte membrane of the membrane electrode assembly of Example 6, there are multiple voids with a height h of 0.4 μm to 0.5 μm, and the width w of the multiple voids in the region with a length of 30 μm in the direction parallel to the interface is 9 μm in total. The membrane electrode assembly of Example 6 has good power generation performance and durability.
[0102] (Example 7)
[0103] A platinum-supported carbon catalyst (TEC10E50E, manufactured by Tanaka Kikinzoku Co., Ltd.), water, 1-propanol, a polymer electrolyte (Nafion (registered trademark) dispersion, manufactured by Wako Junyaku Kogyo Co., Ltd.), and carbon nanofibers (VGCF-H (registered trademark), manufactured by Showa Denko K.K.) were mixed and dispersed using a bead mill to prepare a catalyst ink.
[0104] The produced catalyst ink was directly applied on both surfaces of a polymer electrolyte membrane (Nafion 212 (registered trademark), manufactured by DuPont) using a slot die coater and dried to form an electrode catalyst layer, thereby obtaining a membrane electrode assembly.
[0105] In the membrane electrode assembly of Example 7, there is no void portion at the interface between the electrode catalyst layer and the polymer electrolyte membrane. Therefore, the adhesion between the electrode catalyst layer and the polymer electrolyte membrane is good, and good power generation performance and durability are exhibited.
[0106] (Example 8)
[0107] A membrane electrode assembly of Example 8 was obtained in the same manner as in Example 7 except that the coating amount of the electrode catalyst layer (catalyst ink) on the cathode side was doubled.
[0108] In the membrane electrode assembly of Example 8, there is no void portion at the interface between the electrode catalyst layer and the polymer electrolyte membrane. Therefore, the adhesion between the electrode catalyst layer and the polymer electrolyte membrane is good, and good power generation performance and durability are exhibited.
[0109] (Example 9)
[0110] A membrane electrode assembly of Example 9 was obtained by the same procedure as in Example 7 except that a ball mill disperser was used to disperse the catalyst ink.
[0111] Compared with the catalyst ink of Example 7 dispersed by a bead mill disperser, the dispersion degree of the catalyst ink of Example 9 is lower. As a result, at the interface between the electrode catalyst layer and the polymer electrolyte membrane of the membrane electrode assembly of Example 9, there are multiple voids with a height h of 0.3 μm to 0.4 μm, and the width w of the multiple voids in the region with a length of 30 μm in the direction parallel to the interface is 6 μm in total. The membrane electrode assembly of Example 9 has good power generation performance and durability.
[0112] (Example 10)
[0113] The membrane electrode assembly of Example 10 was obtained by the same procedure as in Example 7 except that an alloy-based carbon catalyst of platinum and cobalt was used instead of the platinum-supporting carbon catalyst.
[0114] Compared with the ink of Example 7, the catalyst ink of Example 10 had cracks in a part of the electrode catalyst layer when applied to the polymer electrolyte membrane. As a result, at the interface between the electrode catalyst layer and the polymer electrolyte membrane of the membrane electrode assembly of Example 10, there were multiple voids with a height h of 0.1 μm to 0.2 μm, and the width w of the multiple voids in the region with a length of 30 μm in the direction parallel to the interface was 10 μm in total. The membrane electrode assembly of Example 10 had good power generation performance and durability.
[0115] (Example 11)
[0116] The membrane electrode assembly of Example 11 was obtained by the same procedure as in Example 7 except that carbon nanotubes (NC7000 (trademark), manufactured by Nanocyl) were used as the fibrous material instead of carbon nanofibers.
[0117] In the membrane electrode assembly of Example 11, no void portion existed at the interface between the electrode catalyst layer and the polymer electrolyte membrane, so that the adhesion between the electrode catalyst layer and the polymer electrolyte membrane was good, and good power generation performance and durability were exhibited.
[0118] (Comparative Example 1)
[0119] A membrane electrode assembly of Comparative Example 1 was obtained in the same manner as in Example 1 except that Nafion 212 (registered trademark) manufactured by DuPont was used as the polymer electrolyte membrane.
[0120] In the membrane electrode assembly of Comparative Example 1, wrinkles and cracks were generated in the electrode catalyst layer, and the power generation performance and durability were reduced. At this time, at the interface between the electrode catalyst layer and the polymer electrolyte membrane, there were multiple voids with a height h of 0.1 μm to 0.3 μm, and the width w of the multiple voids in the region with a length of 30 μm in the direction parallel to the interface was 16 μm in total.
[0121] (Comparative Example 2)
[0122] A membrane electrode assembly of Comparative Example 2 was obtained in the same manner as in Example 1 except that the membrane electrode assembly was produced by a method in which the catalyst ink was applied to a transfer substrate and then transferred to a polymer electrolyte membrane.
[0123] In the membrane electrode assembly of Comparative Example 2, voids with a height h exceeding 0.5 μm were generated at the interface between the electrode catalyst layer and the polymer electrolyte membrane, resulting in reduced power generation performance and durability.
[0124] (Comparative Example 3)
[0125] A membrane electrode assembly of Comparative Example 3 was obtained in the same manner as in Example 1 except that the coating amount of the electrode catalyst layer (catalyst ink) on the cathode side was 4 times.
[0126] In the membrane electrode assembly of Comparative Example 3, wrinkles and cracks were generated in the electrode catalyst layer, and the power generation performance and durability were reduced. At this time, at the interface between the electrode catalyst layer and the polymer electrolyte membrane, there were multiple voids with a height h of 0.1 μm to 0.3 μm, and the width w of the multiple voids in the region with a length of 30 μm in the direction parallel to the interface was 13 μm in total.
[0127] (Comparative Example 4)
[0128] A membrane electrode assembly of Comparative Example 4 was obtained in the same manner as in Example 7 except that the membrane electrode assembly was produced by a method in which the catalyst ink was applied to a transfer substrate and then transferred onto a polymer electrolyte membrane.
[0129] In the membrane electrode assembly of Comparative Example 4, voids with a height h exceeding 0.5 μm were formed at the interface between the electrode catalyst layer and the polymer electrolyte membrane, resulting in reduced power generation performance and durability.
[0130] (Comparative Example 5)
[0131] A membrane electrode assembly of Comparative Example 5 was obtained in the same manner as in Example 7 except that the coating amount of the electrode catalyst layer (catalyst ink) on the cathode side was 4 times.
[0132] In the membrane electrode assembly of Comparative Example 5, wrinkles and cracks were generated in the electrode catalyst layer, and the power generation performance and durability were reduced. At this time, at the interface between the electrode catalyst layer and the polymer electrolyte membrane, there were multiple voids with a height h of 0.1 μm to 0.3 μm, and the width w of the multiple voids in the region with a length of 30 μm in the direction parallel to the interface was 14 μm in total.
[0133] Explanation of symbols
[0134] 1···Solid polymer fuel cell
[0135] 2···Polymer electrolyte membrane
[0136] 3A, 3F... Electrode catalyst layer
[0137] 4A, 4F···Gas diffusion layer
[0138] 5A, 5F... Partition
[0139] 6A, 6F...Gas flow path
[0140] 7A, 7F...Cooling water passage
[0141] 8···Electrode catalyst layer
[0142] 9···Polymer electrolyte membrane
[0143] 10···Catalyst
[0144] 11···Carbon particles
[0145] 12···Polymer electrolyte
[0146] 13···Fibrous substances
[0147] 14···Gap
Claims
1. A membrane electrode assembly for a solid polymer fuel cell, in, Electrode catalyst layers are stacked on both sides of the polymer electrolyte membrane. The electrode catalyst layer contains a catalyst, carbon particles, a polymer electrolyte, and a fibrous substance. There is no void portion at the interface between the electrode catalyst layer and the polymer electrolyte membrane.
2. The membrane electrode assembly for a solid polymer fuel cell according to claim 1, in, The fibrous material includes one or more selected from carbon nanofibers, carbon nanotubes, electrolyte fibers, and oxynitride fibers.
3. The membrane electrode assembly for a solid polymer fuel cell according to claim 1 or claim 2, in, The electrode catalyst layer has a thickness of 20 μm or less. 4 . A polymer electrolyte fuel cell comprising the membrane electrode assembly for a polymer electrolyte fuel cell according to claim 1 or claim 2 . 5 . A polymer electrolyte fuel cell comprising the membrane electrode assembly for a polymer electrolyte fuel cell according to claim 3 .
Citation Information
Patent Citations
Manufacturing method of membrane electrode assembly for fuel cell
JP2009176518A
